Les connecteurs argumentatifs dans le discours judiciaire : approche comparative trilingue (français, italien, roumain) - Chiara Preite; Daniela Dincă (MediAzioni, 2023)
The construction of judicial argumentation favors a massive use of discourse markers during the reasoning in order to guarantee the coherence and cohesion of judgments. Thus, we propose a comparative analysis of the argumentative markers in the judgments of the Court of Justice of the European Union (CJEU) in three Romance languages: French (procedural language), Italian and Romanian, in order to highlight how judges make extensive use of cohesive elements to tighten the linguistic structure of their texts and thus strengthen the coherence of their judgment to make it irrefutable. Since this objective must be achieved in all the EU languages, we shall examine both the influence that the procedural language - French - has on the others - Italian and Romanian -, to determine to what extent translators respect the French legal tradition, and the possible formation of translation equivalents.